Developments in laser processing of optical fibre radiation sensors - Ioannou, Andreas; Christofi, Aristi; Zarvou, Sotia; Kalli, Kyriacos; Jackson, David A.; Kam, Wern; Woulfe, Peter; O’Keeffe, Sinead; Sullivan, Francis J. (My University, 2021)
We present simple and robust designs for optical fiber radiation sensors for dosimetry applications, focusing on improved light gathering efficiency. More specifically, we examined the implementation of compound parabolic concentrators (CPC) using scintillator-based optical fibers. The fabrication of the parabolic concentrator is achieved by femtosecond micromachining at the end face of the polymer fiber. Furthermore, we consider the luminous properties of Gadolinium Oxysulfide (GADOX), an inorganic compound usually used in ceramic scintillators, as an alternative and combine it with laser-shaped polymer optical fibers (POF). The simplicity and ease of implementation of the sensor designs offers the prospect of distributed sensors; adding a wavelength shifting element is discussed to make the sensor more adaptable depending on the selected interrogation system.
Keywords: Femtosecond laser micromachining; Radiation optical fiber sensors; Scintillating material